The profitability of technical analysis during the COVID-19 market meltdown - Camillo Lento; Nikola Gradojevic (Journal of Risk and Financial Management, 2022)
This article explores the profitability of technical trading rules around the COVID-19 pandemic market meltdown for the S&P 500 index, Bitcoin, Comex gold spot, crude oil WTI, and the VIX. Trading rule profits are estimated from January to May 2020, including three sub-periods, on a high-frequency data set. The results reveal that the trading rules can beat the buy-and-hold trading strategy. However, only the Bollinger Bands and trading range break-out rules become profitable after transaction costs during the market crash. Moreover, it is found that composite trading signals effectively improve the profitability of technical analysis around the COVID-19 market crash.
Keywords: 650; COVID-19; market efficiency; technical analysis; technical trading